The Gift: Matricentric Feminism, Physiological Mothering, and Art Practice - Holmes, Allegra (Journal of the Motherhood Initiative for Research and Community Involvement, 2019)
In this article, I explain how the specific politics of mothering shaped my understanding and approach to feminism and how I engage with these ideas in my art practice. I discuss two of my artworks and outline how these works function as tangible realizations of matricentric feminist concepts, specifically the invisibility and disparagement of motherwork and the mother-baby dyad. I suggest how the specific use of the ceramic material creates layered meanings and how my artworks function as concrete objects that speak about intangible ideas. In addition to this, I examine my mother’s mothering practice and how she and my father unintentionally raised their children in a matricentric feminist manner. I contend that growing up in a family that respected, protected, and supported the mother-baby dyad laid the groundwork for me to achieve empowered mothering. I extend this analysis to my own marriage and assert that the re-establishing of subjectivity necessitated by physiological mothering practices is beneficial to the entire family unit. Physiological mothering practices bolstered by matricentric feminism create a space for the renegotiating and dismantling of traditionally gendered roles within the family. I argue that by centring matricentric feminism in social discourse, this dismantling of patriarchal structures can extend throughout society.